HABITAT DAN ASOSIASI PASAK BUMI (Eurycoma Longifolia Jack) DI BUKIT BENUAH KECAMATAN SUNGAI AMBAWANG KABUPATEN KUBU RAYA - Sinambela, Sinta u; Burhanuddin, .; Kartikawati, S M (Universitas Tanjungpura, 2017)
Pasak bumi is one of West Kalimantan's endemic forest products that has high economic value, which has many benefits in medicine. The purpose of this research is to investigate the habitat condition and pasak bumi (eurycoma longifolia jack) association in Bukit Benuah Sub-district of Sungai Ambawang District Kubu Raya. Data collected population, habitat, association, soil, climate, and topography. The condition were survey method, purposive sampling technique single plot, with a plot size of 20 x 20 m, that 0,24 ha . Results showed that population pasak bumi in Bukit Benuah found as many as 22 individuals. The physical condition of the Pasak Bumi (Eurycoma longifolia Jack) habitat in Bukit Benuah is in the altitude between 90 - 120 m dpl. The soil fertility status of the area is low, the type of soil is Podsolik Merah Kuning (PMK), has a smooth texture and included in clay class (clay), with average soil 6,18 pH.Â The slope of the hill is rather sloping and the area is not flooded. The dominant vegetation type means acacia with INP 101,4%, kemayan with INP 81,34%, keranji with INP 49,28%, leban with INP 34,98%, durian with INP 23,65%. Species associated with pasak bumi are Acacia mangium, Diospyros macrophylla BI., Microcos tomentosa Sm., Dialium Indicum L, Durio zibethinus Murr, Vitex pinnata.Keywords: Association, Habitat, Pasak bumi (Eurycoma longifolia Jack)